Dynamic tests and adaptive control of a bottoming organic Rankine cycle of IC engine using swash-plate expander. (15th October 2016) - Torregrosa, A.; Galindo, J.; Dolz, V.; Royo-Pascual, L.; Haller, R.; Melis, J.
Highlights: An experimental testing of a bottoming Rankine Cycle is presented and applied to a 2 l turbocharged gasoline engine. Both stationary and transient tests were performed, including the NEDC cycle. Indicated diagrams of the swash-plate expander during these transients were presented and analyzed. Abstract: This paper deals with the experimental testing of a bottoming Organic Rankine Cycle (ORC) integrate in a 2 l turbocharged gasoline engine using ethanol as working fluid. The main components of the cycle are a boiler, a condenser, a pump and a swash-plate expander. Both steady and transient tests were performed in three engine operating points to understand the behavior and inertia of the system. Pressure-Volume diagram during these transients were presented and analyzed. Operating parameters of the expander, such as expander speed and boiler power, were shifted. The objective of these tests is to understand the inertia of the system and to have a robust control in all the possible transient tests. New European Driving Cycle was tested with and without the expander because it is supposed to represent the typical usage of a car in Europe. It was used to validate the control of the ORC in realistic dynamic conditions of the engine. The importance of each parameter was analyzed by fixing all the parameters, changing each time one specific value. The main result of this paper is that using a slightly simple and robust control based on adaptive PIDs, the two dynamic effects of an ORC could be taken into account, i.e. high inertia effects (boiler and condenser) and low inertia effects (pump and volumetric expander).